Formulation Development and Characterization of Nanoemulsion-based Gel for Topical Application of Raloxifene Hydrochloride - Singh, Tej Pratap; Ahmad, Farhan Jalees; Jain, Gaurav Kumar; Verma, Navneet (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Nanoemulsion-gels are nanosized droplets, and thermodynamically stable oil-in-water dispersion. Raloxifene hydrochloride a selective estrogen receptor modulator currently its more research is being laid on in treatment of diseases in estrogen deficient postmenopausal women. Objectives: The objective of this research was to formulate nanoemulsion-gel of raloxifene for topical delivery. Materials and Methods: The oil, surfactant and cosurfactant were selected on the basis of maximal solubility of raloxifene. The screening of surfactant and cosurfactant were on the basis of their emulsification efficacy with oil to form homogenization mixture on gentle shaking. The nanoemulsions were prepared by ternary phase diagram method using different ratio of oil and surfactant-cosurfactant mixture (Smix) and nanoemulsion region obtained by excel sheet design triangular software. Results: The composition of the optimized nanoemulsion contains 0.072 %w/v raloxifene, 14.29 %v/v oil phase (Labrafil-M2125CS), 33.33%v/v Smix (Cremophor-RH40:Transcutol-P, 1:1), and 52.38%v/v distilled water. The optimized nanoemulsion was converted into gel form by addition of 1%w/v Carbopol-934. The formulation NEG2 possessed droplets size 56.73±0.58 nm, zeta-potential -22.20±0.02 mV, spreadability 18.35±0.45 gcm-1sec-1 and viscosity 98.54±0.39 mPas. The ex vivo permeation of NEG2 (22.38%) was comparatively lower to the permeation of NE3 (26.68%). Also, flux of NEG2 (11.96±0.4 µgcm-2h-1) significantly lower permeability than NE3(16.28±0.7µgcm-2h-1). But nanoemulsion-gel form is maintained more effective concentration within skin due to adhesive nature of gel form remain contact on the applied area for a long duration. Nanoemulsion-gel found stable during six months. Conclusion: The outcome of this study points out the nanoemulsion-gel better than nanoemulsion because of adhesive nature and less permeability. Consequently, It maintain more raloxifene concentration at applied skin.
Keywords: Raloxifene hydrochloride; Nanoemulsion gel; Ternary phase diagram; Zeta potential; Permeation